Assessment of indigenous knowledge of medicinal plants used for livestock treatment in five selected Kebeles of Kersa District, Jimma Zone, South Western Ethiopia - Gemechu, Emiru Chimdessa (Journal of Scientific Agriculture, 2021)
Plants have been a source of medicine in Ethiopia from time immemorial to treat different human and livestock ailments. The purpose of this study was to identify the medicinal plant species and associated indigenous knowledge in livestock treatment. A cross-sectional study was conducted to assess indigenous knowledge of local people on medicinal plants used for livestock treatment in five selected kebeles of kersa district from March to June 2014. A total of 40 traditional healers (33 male and 7 male) 7-9 from each study sites were selected purpouvely with the help of knowledgeable elders, local authorities and kebele leaders. Ethno botanical data regarding plant species, plant parts used, livestock disease treated, and method of preparation and route of administration were collected through structured interview and field observation. A total of 33 plant species distributed in 24 families were identified in the study area. The majority of the medicinal plants 63.63% were collected from the wild and 33.33% from home garden. The major growth habit of the medicinal plants identified in the study area were herbs 39.39%, followed by shrubs 33.33%.The most frequently harvested plant parts were leaves and roots with proportion of 57.7% and 21.21%, respectively followed by seeds (9.09%) and fruits (6.06%). Pounding and crushing were the most commonly used method of remedies preparation whereas the widely used method of administration is oral. The study reveals that the local people of the study area harvest medicinal plants used to treat livestock health problem from the wild habitat. Therefore, awaring the local people of the study area to conserve medicinal plants in their home garden is recommended.